2021
DOI: 10.3390/coatings11070848
|View full text |Cite
|
Sign up to set email alerts
|

Improving the CO and CH4 Gas Sensor Response at Room Temperature of α-Fe2O3(0001) Epitaxial Thin Films Grown on SrTiO3(111) Incorporating Au(111) Islands

Abstract: In this work, the functional character of complex α-Fe2O3(0001)/SrTiO3(111) and Au(111) islands/α-Fe2O3(0001)/SrTiO3(111) heterostructures has been proven as gas sensors at room temperature. Epitaxial Au islands and α-Fe2O3 thin film are grown by pulsed laser deposition on SrTiO3(111) substrates. Intrinsic parameters such as the composition, particle size and epitaxial character are investigated for their influence on the gas sensing response. Both Au and α-Fe2O3 layer show an island-type growth with an averag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The real-time ethanol sensing was performed for all four morphologically variated SrTiO 3 nanostructured based at 150 °C in the presence of 80% RH. In figures 7(a)-(d), all the sensors responded in a positive direction of the y-axis unfolding the p-type semiconducting behavior of the SrTiO 3 nanostructures [24]. The p-type conductivity of the SrTiO 3 nanoforms possibly originated from the p-TiO 2 nanoparticles used in hydrothermal synthesis [29].…”
Section: Sensor Studymentioning
confidence: 94%
See 1 more Smart Citation
“…The real-time ethanol sensing was performed for all four morphologically variated SrTiO 3 nanostructured based at 150 °C in the presence of 80% RH. In figures 7(a)-(d), all the sensors responded in a positive direction of the y-axis unfolding the p-type semiconducting behavior of the SrTiO 3 nanostructures [24]. The p-type conductivity of the SrTiO 3 nanoforms possibly originated from the p-TiO 2 nanoparticles used in hydrothermal synthesis [29].…”
Section: Sensor Studymentioning
confidence: 94%
“…On the other hand, SrTiO 3 and its composites have been successfully employed in sensing different VOCs and gases such as H 2 [12,23], ethanol [3,9,11], O 2 [2,24], ozone [25] and NO 2 [26] but none of them have been focused on the morphology of the resulting sensing layer. The gas sensing performances of nanomaterials are greatly affected by their morphology, crystal structure, surface-to-volume ratio, porosity, oxygen functionality, etc [27].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 196 prepared Au-loaded In 2 O 3 /ZnSnO 3 nanofibers for acetone detection. At 200 °C, 50 ppm response was 19.3, with a fast response/recovery time of 10 s/13 s. Serrano et al 197 reported on α-Fe 2 O 3 epitaxial thin films grown on SrTiO 3 islands functionalized with Au for improved CO and CH 4 detection. The sensitivity of the composite material increased by about 35% and 25% under CH 4 and CO atmospheres, respectively.…”
Section: Compounded Mos Functionalized With Au Npsmentioning
confidence: 99%
“…In addition, hematite has several advantages related to the energy conversion as part of solar cells including a suitable gap [23], and it features a high corrosion resistance and low costs [24]. It also shows a high efficiency as a gas sensor due to the change in its electrical resistance when these compounds are deposited on its surface [25,26]. In paleomagnetism, the solid solutions between hematite and ilmenite (FeTiO 3 ) have interesting magnetic properties depending on the substituted degree of titanium in their structure, and it is used in theoretical and experimental models to explain the remanent magnetization found in magnetic rocks [27].…”
Section: Introductionmentioning
confidence: 99%